INTER SECURE WEBPORTAL SOLUTION (International Journal of Engineering and Computer Science, 2013)
This paper provides security that has to be implemented in the network path. The vital part of this can be effectively programmed so that the data are sent in encrypted form. Among the fool proof algorithms that are in existence we chose RSA to be implement . The factoring challenge was intended to track the cutting edge in integer factorization. A primary application is for choosing the key length of the RSA encryption scheme. Progress in this challenge should give an insight into which key sizes are still safe and for how long. Two thousand forty eight bit is used for security purposes. Web portal give access to multiple users. Security is provided by allowing only authenticated users for accessing websites and files. Authenticated users can be determined by checking against database with the user name and password. The path security can be provided by encrypting the client request using 2048 bit key and can be decrypted by the server with the help of private key which is known only to the server. The accessed detail of every client has been seen in session viewer.